Private Sector Activity in Hong Kong SAR and the Fed : Transmission Effects through the Currency Board - Kang, Joong (IMF Working Papers; Working Paper ;, 2016)
As the U.S. Fed begins to increase the Federal Funds rate, interest rates in Hong Kong SAR will rise in tandem under the Currency Board system. While domestic economic activity in Hong Kong SAR remained resilient in previous rate hike cycles, there is a concern that the impact of higher interest rates would be larger this time due to historic high levels of leverage in both household and corporate sectors. However, macroprudential measures have contained the debt service burden among new borrowers and leverage quality of corporate sector is healthier than its peers in the region. Empirical estimations of aggregate consumption and corporate investment show that private domestic demand is likely to remain robust with the anticipated gradual increase in interest rates over the next few years and taking into account the buffers in the system.